Determinantes das exportações brasileiras: uma análise das elasticidades para os principais parceiros comerciais (2000-2014) - Lima, Victor Jose Rocha de (2019)
This study propose an analyze about the determinants elasticities of the disaggregate by factor aggregate Brazilian exports to the main trade partners from 2000 to 2014. As of international and national trade literature, it was concluded that the main exports determinants are foreign income, real exchange rate, real interest rate and credit emission and the degree of commercial opening. Using the adapted model from Castro & Cavalcanti (1998), as of panel data methodology with fixed effects, the results showed that exist: an increase of income-elasticity of main trade partners demand for basic products; an impact more incisive from the degree of commercial opening on the exports of low aggregate value; an exchange rate appreciation that promoted more the mentioned sectors; effects of credit emission that boosted the exports of basic products. That results showed a stimulus for a depreciation of productive structure, that represents, among other things, according empirical evidences: a bad wages structure; persistent entries on commodity bubbles that promotes an exchange rate appreciation and consequently a decay on the exports of manufacture products; a great external dependence and low international protagonism. This study is relevant to incorporate news information to the empirical evidence actual. Especially because of the analysis from the impacts of the degree of commercial opening and credit emission on the disaggregate by aggregate factor Brazilian exports to main trade partners. Furthermore, this works is important because show informations that helps on the international trade policy’s formulation.